COGNITIVE ASSESSMENT IN HIGHER EDUCATION: AN ANALYSIS OF LINEAR ALGEBRA MIDTERM EXAM ITEM QUALITY - Putri, Reni Albertin; Suwito, Abi; Afifah, Ngizatul; Firmansyah, Frenza Fairuz; Rahmayani, Sekar Ayu; Angrenani, Arin Berliana; Luthfiyah, Ishmah (Jurnal Pendidikan Matematika dan IPA, 2026)
Cognitive assessment is an important part of learning evaluation, including in linear algebra courses. Essay-type exam questions are one of the instruments often used. However, several studies show that there is a lack of item feasibility studies conducted by teachers. This fact prompted this study, which aimed to determine the quality of midterm exam questions in linear algebra courses as cognitive assessment instruments. The study was conducted on a class of second-semester students in the Mathematics Education study program at the Universitas Jember. This descriptive evaluative design using a mixed-methods approach consisted of three stages: planning, implementation, and conclusion drawing. The research instrument consisted of five descriptive questions on linear algebra along with details of the desired learning outcomes. Based on the research, the researcher concluded that, in general, the five questions had met the minimum requirements in terms of validity, reliability, discriminating power, and difficulty index as cognitive assessment instruments for linear algebra learning. However, the researcher found that the average test results of students were still low. Therefore, the researcher urges further research to be conducted with a focus on improving the cognitive abilities of students in linear algebra courses or research on the development of additional cognitive assessments to better measure the abilities of students in linear algebra courses.